The Metaphor of ”Dog” in Egyptian Arabic Proverbs - Syahreni, Jessica Meilia; Ma'nawi, Arief (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2024)
Proverbs that employ metaphors are deeply rooted in the social and cultural life of a society, often drawing from animals and plants. These proverbs reflect the characteristics and identity of a community while delivering messages in an easily understandable manner. This study examines the metaphor of the "dog" in Egyptian proverbs, employing a semantic cognitive and conceptual metaphor approach. The study focuses on the forms of the dog metaphor and its representation in Egyptian Arabic proverbs. A descriptive qualitative research method was used, with data collected using the SBLC method. The data were analyzed through the referential matching method. The study found 11 proverbs that use the word "dog" as a metaphor. The conceptualization of the dog metaphor is predominantly based on the dog's state, drawing on the relationship between humans and dogs as an analogy for human characteristics or conditions. The use of "dog" as a metaphor in these proverbs represents various human traits, including both good and bad characteristics, excessive talkers, lost individuals, as well as communities (civil and governmental) and individual traits.